Lipid rich carcinoma in canine mammary gland with metastasis in the abdominal cavity - Perossi, Isabela F. S.; Martinelli, Paulo E. B.; Bonato, Leticia; Lima, Gabriela P. [UNESP]; Bertolo, Paulo Henrique L. [UNESP]; Costa, Rafael R. M. E. [UNESP]; Gómez, Jorge L. A. [UNESP]; De Nardi, Andrigo B. [UNESP]; Vasconcelos, Rosemeri O. [UNESP] (Brazilian Journal of Veterinary Pathology, 2020)
Lipid-rich carcinoma of the mammary gland is a rare variant of cancer and extremely uncommon in dogs. This case report describes the clinical and histopathological aspects of lipid-rich carcinoma in a female dog. A four-year-old spaeyd German Shepherd dog with enlarged volume adhered to the caudal and inguinal abdominal mammary region was examined. The impossibility of surgical ressection led to euthanasia during the surgical procedure. At necropsy, analysis of the abdominal cavity revealed the presence of an irregularly shaped mass, whitish with red areas, in the intrapelvic region. Also, metastases in axillary and mediastinal lymph nodes and right lung were observed. Histopathological analysis of the tumor in the mammary glands and intrapelvic mass showed malignant neoplastic proliferation of epithelial cells. The cells had a distinct shape and boundary, a well-defined cytoplasm, and the presence of intracytoplasmic macro and micro vacuoles, which sometimes pushed the nuclei to the periphery. The lymph nodes had lost the histological architecture due to metastasis. Marked and diffuse immunostaining of tumor cells in the cytoplasm by pancytokeratin, GATA 3 and 35BH11 confirmed the epithelial origin of the tumor. This very aggressive and uncommon neoplasm should be considered as a possible metastasi in the differential diagnosis of tumors of the abdominal cavity.
Keywords: Cytokeratin; Histology; Immunohistochemistry; Necropsy